Together with a student. Self-assessment method in perfecting and developing text-creating competence - Gryboś, Monika (Activation-innovation-inspiration in (glotto) didactics, 2022)
The assumptions, process and aims of the method by Ewa Nowak were described in the article. The method is used to shape text-creating competence and is addition to traditional methods by Anna Dyduchowa. The author of the article, on the basis of her own teaching experiences, finds the self-assessment method useful in developing students' abilities on different levels. This method focuses on text-creating competence, supports personality development and gaining the soft competence.